2010
DOI: 10.1103/physrevc.82.035201
|View full text |Cite
|
Sign up to set email alerts
|

Quarkonia and heavy-quark relaxation times in the quark-gluon plasma

Abstract: A thermodynamic T -matrix approach for elastic two-body interactions is employed to calculate spectral functions of open and hidden heavy-quark systems in the quark-gluon plasma. This enables the evaluation of quarkonium bound-state properties and heavy-quark diffusion on a common basis and thus to obtain mutual constraints. The two-body interaction kernel is approximated within a potential picture for spacelike momentum transfers. An effective field-theoretical model combining color-Coulomb and confining term… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 77 publications
5
86
0
Order By: Relevance
“…On the other hand our results differ significantly from the spectra obtained in the T-matrix study of ref. [60]. There the authors use purely real model potentials which lead to in-medium states that appear to possess a significantly larger energy than their vacuum counterparts.…”
Section: Jhep12(2015)101mentioning
confidence: 99%
“…On the other hand our results differ significantly from the spectra obtained in the T-matrix study of ref. [60]. There the authors use purely real model potentials which lead to in-medium states that appear to possess a significantly larger energy than their vacuum counterparts.…”
Section: Jhep12(2015)101mentioning
confidence: 99%
“…A next-to-leading order (NLO) computation in perturbation theory indicates the presence of a large correction towards strong interactions [12], and strong interactions have also been observed in N = 4 Super-Yang-Mills theory [13][14][15][16]. Furthermore classical lattice gauge theory simulations [17] and analyses in the confined phase [18][19][20][21][22] are consistent with strong interactions, and various other approaches are being pursued in the same vein [23][24][25][26][27][28][29] (for a review, see ref. [30]).…”
Section: Introductionmentioning
confidence: 99%
“…The second choice is inspired by Ref. [41] which showed that a non-decreasing drag coefficient near the phase transition is favored for a simultaneous description of heavy flavor R AA (p T ) and v 2 (p T ) (this is also supported by T -matrix calculations [42,43]). These models are fairly simple to implement and they give a good description of R AA .…”
Section: Details Of the Modelmentioning
confidence: 99%